Determining the optimum digestible isoleucine to lysine ratio for Ross 708 x Ross YP male broilers from 0 to 18 d of age - A.T. Brown (Elsevier, 2022)
SUMMARY: Continuous genetic improvement of high yielding broiler strains necessitates reevaluation of amino acid requirements. The objective of this study was to evaluate the dIle requirement of Ross 708 x Ross YP male broilers from d 0 to 18. Experimental diets were created from a common deficient corn and soybean meal-based diet providing a dIle:dLys of 52%; after manufacturing, half was retained for the creation of the summit diet (82% dIle:dLys). The remaining 5 experimental diets ranged from 57 to 77% dIle:dLys and were blended proportions of deficient and summit dIle diets. A practical control diet (PRAC-CON; 67% dIle:dLys) was manufactured separately for verification of the blended control diet (50 deficient:50 summit blend; BLEND-CON; 67% dIle:dLys); all diets were subsequently pelleted/crumbled. On d of hatch, 2,400 male chicks were equally allocated to 96 pens (12 replications/treatment). All dIle:dLys ratios were estimated using quadratic regression (QR; 95% of the asymptote), as well as linear and quadratic broken line models (LBL; QBL). Performance data demonstrated that feeding higher than starter breed nutrient specifications, for broilers, at the time of this study (67% dIle:dLys) improved broiler performance from 0 to 18 d. After considering the estimated requirements produced by the multiple regression models for all measured variables (BW, BW gain, FCR, and CV of ending BW), these data suggest that the optimum starter dIle:dLys ratio for male Ross 708 × Ross YP broilers from 0 to 18 d, ranged from 63 to 74% dIle:dLys. Further research should evaluate dIle:dLys requirements of male Ross 708 × Ross YP broilers during the remaining grow-out phases.